Posterior reversible encephalopathy syndrome in the puerperium: a case report. Issue 1 (19th January 2022) - Dunphy, Louise; Kothari, Trusha; Ford, Jonathan
Abstract : Headache is a common presentation to the physician. Although most causes of a headache in pregnancy are benign, the pregnant woman is at risk of a life-threatening secondary headache such as eclampsia, venous sinus thrombosis or posterior reversible encephalopathy syndrome (PRES). Pregnancy and the puerperium are prothrombotic risk factors. Although the aetiology of PRES remains to be fully elucidated, hypertension with failed autoregulation results in brain oedema. An alternative hypothesis includes endothelial injury and hypoperfusion leading to an alteration in the integrity of the blood-brain barrier. It occurs in complex, systemic conditions such as pre-eclampsia, following bone marrow transplantation, chemotherapy, sepsis and autoimmune diseases. The most common clinical presentation is headache, altered alertness, seizures and visual disturbance such as hemianopia, visual neglect and cortical blindness. It can also develop in normotensive individuals. Symmetric vasogenic oedema in a watershed distribution involving the parieto-occipital regions are typically evident on MRI. Management is determined by the underlying aetiological risk factor. The authors present the case of a 32-year-old multiparous woman presenting with tonic-clonic seizures 16 days following an elective caesarean section. Her pregnancy was complicated by hypertension and headache. There was no history of pre-eclampsia. She required intubation and ventilation. The diagnosis of PRES was established on MRI. Early recognition and treatment provide a favourable prognosis as the clinical symptoms and imaging characteristics are reversible in a large cohort of affected individuals.